“Automatización del parqueadero con direccionamiento a los lugares de estacionamiento y control de acceso en la puerta principal del bloque ``b´´ de la Universidad Técnica de Cotopaxi extensión La Maná”. - Abrigo Vivas, Robinson Fabricio (2022)
The growing increase in the university population together with the use of vehicles is reflected in a traffic congestion on the main streets of the University and therefore a greater requirement for parking spaces, which is a stressful task that generates a considerable loss of time both To teachers, students and administrative staff, this problem interrupts us during academic hours with the noise produced by the vehicles and it becomes a tedious environment for both students and teachers. The development of the internet of things better known as IoT allows us to create a Smart University to manage university resources and provide a better quality of life to the university community. This project focused on developing and implementing an intelligent parking system with access and control to the main door of block B of the Technical University of Cotopaxi Extension "La Mana". The access control to the main door is connected through an application that allows us to open and close it from the comfort of your vehicle, both for security and comfort; When entering, the user will be able to see on a screen the parking lots that are available and will go to the closest or feasible place for the user. The enhancement provided by this project has been successfully received both at the University and within the canton due to its correct functionality. .